2018
DOI: 10.1002/ecy.2221
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling changing interspecific interactions across environmental gradients using Markov random fields

Abstract: Inferring interactions between co-occurring species is key to identify processes governing community assembly. Incorporating interspecific interactions in predictive models is common in ecology, yet most methods do not adequately account for indirect interactions (where an interaction between two species is masked by their shared interactions with a third) and assume interactions do not vary along environmental gradients. Markov random fields (MRF) overcome these limitations by estimating interspecific interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 28 publications
1
109
0
Order By: Relevance
“…Here, we have demonstrated that graphical network models can untangle how interspecific interactions can shape gut microbial communities in moose. Additionally, we show that MRF and CRF models can robustly construct co-occurrence networks (Clark et al, 2018b) and, coupled with taxonomic and functional information, find high-resolution insights into interspecific associations. Graphical network models, as with other correlation-based approaches, do have limitations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Here, we have demonstrated that graphical network models can untangle how interspecific interactions can shape gut microbial communities in moose. Additionally, we show that MRF and CRF models can robustly construct co-occurrence networks (Clark et al, 2018b) and, coupled with taxonomic and functional information, find high-resolution insights into interspecific associations. Graphical network models, as with other correlation-based approaches, do have limitations.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the roles that interspecific associations play in governing the assembly of microbial systems (microbial interspecific associations) are less understood (Ganz et al, 2017;Herren & McMahon, 2018;Zelezniak et al, 2015), particularly for within-host microbial communities. Even when microbial interspecific associations are quantified in communities, the relative importance of microbe dispersal (Evans, Martiny, & Allison, 2017;Zhou & Ning, 2017) and host characteristics in shaping microbial communities is rarely assessed (Clark, Wells, & Lindberg, 2018b). The quantification of interspecific associations of gut microbes is rare in wildlife populations but, given the significant ecological insights derived from studies of human gut microbial communities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Let t 1 represent the first year of detection in a cell; we estimated the recurrent probability (RP) after x years from a reference year t as the conditional probability RP ( x , t ) = Prob(DY ( t 1 , t + x ) = T + 1|DY ( t 1 , t ) = T ), where RP (1, t ) represents the transmission rate for the recurrence immediately after year t and T represents the number of detection years (Clark et al. ). The RP was computed for 166 infested cells based on their time series (58‐yr) from 1960 to 2017.…”
Section: Methodsmentioning
confidence: 99%
“…represents the transmission rate for the recurrence immediately after year t and T represents the number of detection years (Clark et al 2018). The RP was computed for 166 infested cells based on their time series (58-yr) from 1960 to 2017.…”
Section: Invasion Pattern and Recurrence Probabilitymentioning
confidence: 99%
“…Associations can also be generated indirectly through species responding in similar (or opposing) ways to environmental gradients or habitats (Dunstan, Foster, & Darnell, 2011;Warton et al, 2015). Furthermore, relationships among species vary in time and space under changing biotic or abiotic conditions (Clark, Wells, & Lindberg, 2018); for example, species may only compete when resources are limiting (Perry, Mitchell, Zutter, Glover, & Gjerstad, 1994), in certain parts of their range (Pacala & Roughgarden, 1985), or in the absence of predation (Chase et al, 2002).…”
Section: Introductionmentioning
confidence: 99%